The Reality of Prison Libraries in the Hashmiat Kingdom of Jordan from the Point of View of their Employees - Al –Jaradat, Omar Mohammad (2018)
This study aims to identify the reality of prisons libraries in the Hashmiat Kingdom of Jordan, identify the different aspects of this reality, and evaluate the strengths and weaknesses of their resources, systems and services in order to present a proposal for improvement and development of them. The study aims to know the views of prisoners in prison libraries In terms of their reality, practice and contents.The study has used questionnaire and interview tools to answer the study questions and test its hypotheses. The questionnaire was distributed to a sample of (52) prisoner representing (88%) of the study target society , which includes workers and working inmates in prison libraries in Jordan.The results of the study show that all prison inmates need different libraries to get information and improve their knowledge. The result also show that there is no relation between the existence of a prison library and the education and cultural background of the prisoners ,the lack of flexibility in the future for expansion of the library. The results also show a shortage in the financial support to fund the prison libraries in general, as well as the lack of qualified and trained clerks.According to the results, the study introduces many recommendations hoping they will be considered by the managers and decision makers. The most important of these recommendations is the need to establish cooperative relationships between prison libraries and other public and privet libraries in the community, which may help to provide more and modern services. Also, the study recommends to courage having administrative decision to establish independent library building in each prison in Jordan. Due to there is a relationship between the existence of a library in the scientific sense inside the prison and the conviction of those responsible for the importance of its role in the reforming and rehabilitation of inmates, the study recommends to pay more attention to the importance of prison libraries